EVALUASI PELAKSANAAN PROGRAM UKGS PADA SISWA SD 091407 DI WILAYAH KERJA PUSKESMAS SARIMATONDANG KABUPATEN SIMALUNGUN TAHUN 2020 - Maria Olivia Sinaga (Jurnal Inovasi Kesehatan Masyarakat, 2020)
ABSTRACT Dental caries in 6-12 years old primary school students is a major dental and oral health problem that requires attention and prevention through the implementation of the School Dental Health Program (SDHP). The purpose of the study was to evaluate the implementation of the SDHP program and analyze the relationship between toothbrush behavior and the incidence (number) of caries and Decay Missing Filled-Teeth Index (DMF-T Index) numbers at Primary School 091407 Sarimatondang in the working area of ​​the Sarimatondang Public Health Center in Simalungun Regency. This type of research uses a mixed methods research approach which is a qualitative method with a case study approach and quantitative with a cross sectional approach. The study was conducted at the Puskesmas Sarimatondang and the time of the study began in December 2019 - April 2020. The informants selected in this study were carried out intentionally (purposive sampling) namely the school principal and supervisor of SDHP. The research sample was all students in Class I - VI totaling 168 students. Data were collected through in-depth interviews and using questionnaires. Data were analyzed by thematic analysis and Pearson correlation. The results showed that the SDHP Program activities at Primary School 091407 Sarimatondang had not been carried out thoroughly. There are 5 M (Man, Money, Material, Method, Machine) obstacles in the implementation of the SDHP Program. There is a relationship between toothbrush behavior (knowledge) with the incidence (number) and DMF-T Index number. It is recommended that SDHP supervisors should take part in training to increase their knowledge and insights on dental health and at the same time act as a mobilizer for SDHP activities. Principals make schedules for the overall implementation of the SDHP program and It carried out routinely and the Head of Sarimatondang Puskesmas supports and implements SDHP activities in accordance with the Guidelines School Dental Health (SDHP) Program established by the Indonesian Ministry of Health in 2012.